Caracterização dos lençóis maranhenses e dunas inativas (fósseis): implicações paleoambientais - Gastão, Francisco Gleidson da Costa (2010)
Climate change covering centuries or decades can produce important ecological variations altering the Earth natural scenarios, as well as, endangering human welfare and others being livings. For this reason, it’s important to study climatic evolutions during Quaternary, since trough the knowledge the weather conditions in the past we can anticipate future conditions. The inactive aeolian dune fields regionally distributed, are considered sedimentologic and geomorphologic indicators of paleoclimatic changes during Quaternary. The Maranhão state coast shows perhaps the greatest aeolian record of Brazilian littoral which includes active dune fields (Lençóis Maranhenses) inactive dunes (fossil) covering a 1,000,000 hectares surface. It was held in this dissertation a dunar evolution study, setting up the several dunes types formation chronology, climatic and paleoenvironmental conditions through remote sensing techniques using Landsat 5, Landsat 7, Quickbird and radar SRTM satellites images, field survey and laboratory analysis. The region morphology is composed of three types of relief: dune bodies (active and inactive), pre-coastal tabuleiros and dissect tabuleiros. Linear structures that occur in this region are responsible for morphologic features and control the hydrographic patterns: parallel, rectangular, dendritical and contorted. There are four evolution phases that correspond to the formation of aeolian deposits. The first one was formed 123.000 years B.P. during the highest of Last Transgression, when the sea eroded total or partially the ancient continental sediments. These dunes now have a reddish tint and they have lost the original form. The second phase has been developed during glaciations between 70 and 60 years B.P. and sea level was lower than the actual, providing sediments to produce a sand desert. These active dunes from Pleistocene were, subsequently fixed that correspond to the third phase. The last one is marked by the active dunes (Lençóis Maranhenses) that keep on moving. Climatic and environmental changes during Quaternary are related to the genesis and evolution of Aeolian sand deposits, according to the regional dunes sedimentology and morphology